(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2005)
Clinical behavior analysis, in opting for radical behaviorism, focuses on transformation (and not on representation), on interaction (and not on causality), on action (and not on being). Because of these choices, clinical behavior analysis needs an ethic of relating (and not an ethic of the profession as an entity). This essay suggests that a radical behaviorist ethic for clinical practice is possible. The possibility of such an ethic is explored from the beginnings of nominalist philosophy, the ideas of Buridan and the reflections of radical behaviorist authors. An analysis of social interactions through the concept of contingency has implications for the understanding of feelings and their role of reference in ethics. This behavioristic ethic will necessarily be complex because the therapeutic relation is constructed within multiple contexts, like that of culture, health politics, economy, the restricted universe of the client’s life and that of the therapist.